Phytochemical Constituents of Cnestis ferruginea and Its Toxicity in Fish - Teslim Asefa Ojetayo; Abiola Fadilat Durojaiye; Nathanel Akinsafe Bamidele; Odunayo Rukayat Ibitunde; Oluwaseun Abigail Sofowote (Jurnal Perikanan Universitas Gadjah Mada, 2022)
The study explored the potentials of C. ferruginea as a nutritional supplement while also testing its possible toxicity to fish. Standard proximate and mineral analysis procedures were used to estimate nutritional composition, while Lorke's and Tainter and Miller's methods were used to determine LD50 of C. ferruginea. Results were presented as means±SD, and analysis of variance was used to test for differences in means. The values obtained for each parameter measured were significantly different (p<0.05) across all the samples. The analyzed ash contents for the crude powder, aqueous, ethanolic extracts were 1.47±0.02, 1.06±0.01, and 0.85±0.01,respectively. A low protein concentration of less than 5% was recorded across the samples. A decreasing trend (75.05±0.25 < 52.09±0.19 < 31.21±0.61) was observed in the carbohydrate values in the crude powder, aqueous and ethanolic extracts, respectively. The mineral composition of C. ferruginea across the samples was significantly different (p<0.05). The crude powder sample had the highest values recorded for all the minerals analyzed, followed by the aqueous and then ethanolic extract except for iron and copper, where ethanolic extract had higher values than aqueous extract. The values obtained for alkaloids, flavonoids, saponin, tannin, phenolic compounds, and oxalates showed a significant increase (p<0.05) in the crude powder sample, aqueous extract, and ethanolic extract, respectively. However, the ethanolic extract had higher values than the aqueous extract for glycosides, terpenoids, and steroids. Of the phytochemical components analyzed, oxalate had the highest value (16.11±0.01) followed by saponin (12.31±0.19), alkaloids (8.12±0.00), and tannin (6.43±0.17). The lowest values were recorded in steroids (0.11±0.00), terpenoids (0.29±0.01), and glycosides (0.34±0.01). LD50 was calculated to be 223.61 mg/kg for aqueous extract of C. ferruginea and 170.29 mg/kg for ethanolic extract (Lorke's method), while 124.82 mg/kg was obtained for aqueous extract and 128.63 mg/kg for ethanolic extract of C. ferruginea (Miller and Tainter method). The behavioural responses observed include weakness, hanging within the water column, and slow response to feeding. Mortality was recorded in some doses. The results indicate that C. ferruginea is a potential source of energy and minerals when incorporated into the fish diet. Its phytochemical constituent is wealthy and could be used in fish health management. However, the plant is toxic and cautiously applied with an LD50 value lower than 2.500 mg/kg.